Reconceiving reparatory justice: transatlantic enslavement, the maangamizi, and the making of international law - Schwarz, Katarina (2019)
In recent decades, a groundswell of public and political attention has turned towards the injustices of the past, and the legacies of antecedent atrocities that resonate in the present. Gradually, presumptions of a linear historical progression (and thus an automatic process of ‘moving on’) are being displaced in favour of recognition of the potential for transgenerational transmission of wrongs. On this account, simply looking forward is insufficient. The past must be acknowledged and accounted for. In the history of international law, this necessarily involves engagement with European expansion into the ‘New World’, and the forced migration and enslavement of over twelve million Africans. Thus, centuries of advocacy and activism coalesce in the contemporary movement for reparatory justice for the system of transatlantic chattel enslavement.